Zirconia Based Dental Biomaterials: Structure, Mechanical Properties, Biocompatibility, Surface Modification, and Applications as Implant - Lin, Hua; Yin, Cuilan; Mo, Anchun (Frontiers in Dental Medicine, 2021)
Zirconia, with its excellent mechanical properties, chemical stability, biocompatibility, and negligible thermal conductivity, is ideal for dental and orthopedic applications. In addition, the biocompatibility of zirconia has been studied in vivo, and no adverse reactions were observed when zirconia samples were inserted into bone. However, their use is controversial among dentists and researchers, especially when compared with mature implants made of titanium alloy. The advantages and limitations of zirconia as biomaterials, such as implant materials, need to be carefully studied, and the design, manufacture, and clinical operation guidelines are urgently required. In this review, the special components, microstructure, mechanical strength, biocompatibility, and the application of zirconia ceramics in biomaterials are detailly introduced. The review highlights discussions on how to implement innovative strategies to design the physical and chemical properties of zirconia so that the treated zirconia can provide better osteointegration after implantation.